Clinical researchPredictors of bone disease in Egyptian prepubertal children with β-thalassaemia major - Tantawy, Azza A.G.; El-Bostany, Eman A.; Matter, Randa M.; El-Ghoroury, Eman A.; Ragab, Shadia (Archives of Medical Science, 2010)
Introduction: Thalassaemic osteopathy is a multifactorial disorder and limited information exists about bone accrual and bone mineral density (BMD) in prepubertal thalassaemic children. The study aimed to investigate some potential genetic and biochemical bone markers as possible early predictors of BMD variations in children with -thalassaemia major (TM) before puberty. Material and methods: Thirt-one prepubertal children with β-TM, and 43 matched controls were subjected to BMD assessment by dual energy X-ray absorptiometry (DEXA). Vitamin D receptor (VDR) gene polymorphisms (Bsm1, Fok1) and the biochemical bone markers serum osteocalcin and propeptide I procollagen (CPIP) and urinary deoxypyridinoline (DPD) excretion were assessed. Results: Bone mineral density was reduced in 25% of thalassaemics at the spine and 15.4% at the hip region. Significantly higher levels of urinary DPD and lower serum osteocalcin and CPIP levels were found in the studied thalassaemic children compared to controls (p < 0.001). A significant negative correlation was present between BMD in spine and hip and the patients’ age (r = –0.6367, p = 0.0002 and r = –0.616, p = 0.00079, respectively). There was a significant reduction in BMD in males compared to females. Reduced BMD was more frequent in male patients with genotypes bb and Ff but not in females. Bone mineral density was not related to the studied biochemical bone markers, mean pre-transfusion haemoglobin or serum ferritin. Conclusions: Routine BMD screening with DEXA is proposed to be a sensitive predictor for early bone changes, particularly at the lumbar spine. DR gene polymorphisms of Bsm1 and Fok1 polymorphisms may be determinants of BMD in Egyptian prepubertal male thalassemics